Calculating leaf surface areas using OpenCV - (:unkn) unknown (My University, 2019)
The script automatically finds areas of up to 4 contours near the corners of a central landmark post-it note for each image in a given folder. The areas in squared centimeters are output into a CSV file in the same folder.
python (>= 3.7.1) script, uses libraries numpy (>= 1.15.4), os, csv, cv2 (>= 4.0)
Keywords: image processing; contour area